2014
DOI: 10.1111/cpr.12109
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNAs as oncogenes or tumour suppressors in oesophageal cancer: potential biomarkers and therapeutic targets

Abstract: MicroRNAs are a class of small, non-coding RNAs that can negatively regulate protein-coding genes, and are associated with almost all known physiological and pathological processes, especially cancer. The number of studies documenting miRNA expression patterns in malignancy continues to expand rapidly, with continuously gained critical information regarding how aberrantly expressed miRNAs may contribute to carcinogenesis. miRNAs can influence cancer pathogenesis, playing a potential role as either oncogenes or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
54
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(57 citation statements)
references
References 69 publications
1
54
0
2
Order By: Relevance
“…Moreover, there is growing evidence that the expression of miRNAs plays an important role in the progress of esophageal cancer (Chu et al, 2013;Hong et al, 2014;Huang et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, there is growing evidence that the expression of miRNAs plays an important role in the progress of esophageal cancer (Chu et al, 2013;Hong et al, 2014;Huang et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Aberrant regulation of miRNAs has been involved in a number of human diseases, including cancers. In tumorigenesis, miRNAs may act as tumor suppressors (5,6) or oncogenes (7,8) in different types of cancers, including esophageal cancer (9). Recent clinical findings indicated that the upregulation of miR-146b was associated with poor survival in esophageal squamous cell carcinoma (10).…”
Section: Introductionmentioning
confidence: 99%
“…MicroRNAs (miRNAs) are a class of small noncoding RNAs that are approximately 23 nucleotides in length (Huang et al, 2014). miRNAs are involved in cell development, differentiation, proliferation, and apoptosis through targeting mRNAs (Bao et al, 2014).…”
Section: Introductionmentioning
confidence: 99%